Berufliche Pflege und soziale Gerechtigkeit: sechs sozialethische Problemanzeigen - Bobbert, Monika (Ethik in der Medizin, 2019)
Problems and conclusions: In Germany, fundamental problems of justice arise in relation to nursing care. Six socio-ethical problems are dealt with, the solution of which has priority when it comes to fairer framework conditions for nursing care: Since every shortage of nursing staff is relevant to human rights in so far as it is not possible to meet the justified entitlements of those in need of nursing care, overcoming the shortage of personnel must have top priority. Secondly, nursing care supervisors distribute a large financial volume from nursing care insurance by means of nursing care grade assessments. For reasons of need justice, it is proposed that nurses orient themselves more closely to the self-image of social work in this task of the welfare state and that further training should be transferred to a course of study. Thirdly, in view of the profound effects of time pressure on nursing interactions and on professional understanding, part of the time compression must be reduced. Fourthly, it is explained which burdens are associated with a high level of sickness and staff shortages and how these risk factors could be countered. Fifthly, resources must be made available to support the special burdens of the nursing profession, and sixthly, structures for ethical counselling should be strengthened to deal with ethical problems and reduce moral stress.